PERCEPÇÃO DOS CONSUMIDORES SOBRE O BEM-ESTAR DE AVES NOS MUNICÍPIOS DE AQUIDAUANA E ANASTÁCIO, MS - ARRUDA, Milena Raiane Silva de; BARONI, Thaís de Abreu Toledo; SANTANA, Patricia Gomes; BAIRROS, Eliane Côrrea; DALEGRAVE, Caroline de Brito; GARCIA, Elis Regina de Moraes (ANAIS DO ENIC, 2024)
-